Detection of local Erwinia Isolates Causing Diseases in Potato by Using DNA Amplification by Polymerase Chain Reaction Technique (PCR) - Mohammed, Maitham J; Selman, Ehab D (Al-Nahrain Journal of Science, 2018)
Seventy samples of infected potato’s tubers were collected from Baghdad city during the period from September 2011 to February 2012. These samples were collected from Alradwaniyah potato’s store/ Albyaa market and from Awrad Alnahar potato’s store in Abu ghraib and two bacterial strains of Erwinia were obtained from Plant Protection department/ College of Agriculture/ Baghdad University. The Crystal Violet Pectate (CVP) used as a selective- diagnostic medium to isolate and purify Erwinia. The strains and isolates of Erwinia were characterized according to the morphology and microscopic characteristics, along with the biochemical tests and API 20E tests. The Erwinia isolates have a positive reaction for Catalase, Raffinose and Cellobiose and a negative reaction for Oxidase and Sorbitol. By using Reagent Genomic DNA Kit method for Total DNA extraction, during electrophoresis process, the results showed that some of selected isolates and the two standard strains of Erwinia contained at least two bands of small plasmid DNA. The identification was confirmed by using DNA amplification by polymerase chain reaction technique (PCR) and Erwinia carotovora subsp. carotovora specific primer such as (Ec001), the selected local isolates of Erwinia and Erwinia carotovora subsp. carotovora ATCC 15713 potato’s pathogen had a positive reaction (one band 312 bp) for the former primer